Generation of TWO iPSC lines (CRICKi009-A; CRICKi010-A) from patients with type 1 von Hippel-Lindau (VHL) and histopathologically confirmed renal cell carcinoma (RCC) - Liani G. Devito; Eugénie S. Lim; Samuel M. O’Toole; Scott T.C. Shepherd; Daqi Deng; Hugang Feng; Taja Barber; William M. Drake; Samra Turajlic; Lyn Healy (Stem Cell Research)
VHL disease is an inherited and autosomal dominant disorder affecting 1 in 36,0000 individuals worldwide. It is caused by von Hippel-Lindau (VHL) gene mutations and can affect both genders and all ethnic backgrounds (Nordstrom-O’Brien et al., 2009; Maher, 2004). Here, we generated and characterised two iPSC lines derived from patients with histopathologically confirmed clear cell renal cell carcinoma (ccRCC) and VHL Type 1 enrolled in the TRACERx Renal (TRAcking Renal Cell Carcinoma Evolution Through Therapy (Rx)). PBMCs were reprogrammed to pluripotency using a genome non-integrating Sendai virus (SeV) vectors protocol. Both human iPSC lines displayed normal morphology, expressed markers associated with stemness and differentiated into the three germ layers. The iPSC lines could be used as a disease-specific cellular model to understand further the inherited disorder of Type 1 von Hippel-Lindau (VHL) disease.